Modern information and communication technologies in the training of junior border guards in the countries of the European Union - Naholiuk, Mykola (Educological discourse, 2024)
The article characterizes modern information and communication technologies (hereinafter - ICT), which are used in the process of basic training of border guards of the countries of the European Union, with the aim of adapting advanced foreign experience to the system of professional training of junior border service inspectors in departmental educational institutions of the Ukrainian border guard agency. It was found that the use of ICT in the process of professional training of border guards allows to optimize the overall professional development of junior inspectors of the border guard service, motivates the personnel of the border guard department to study new material in a convenient way after classroom hours, ensures the implementation of the principles of mobile learning, expands the range of possible exercises and professionally oriented tasks, which contributes to a better involvement of listeners in the process of learning educational content. The development and implementation of educational ICT in the system of professional training of junior inspectors of the border guard service changes the structure of the cognitive activity of the future specialist, which affects the content of education, determines the renewal of forms, methods and principles of training focused on the use of their independence. The authors sate that considered modern ICT based on web platforms of law enforcement agencies of the European Union countries allow junior border guard service inspectors to take an active position in the process of mastering new knowledge, to independently determine the order, pace, and method of acquiring knowledge, and is currently a key element of the professional training of junior border guard service inspectors in the departmental educational institutions of the Ukrainian border guard agency.